Impressions Of A Frenchman About The Balkans In The XVIII Century - Galunov, Todor (Sociološki pregled, 2020)
The paper gives an overview of Dalibor Elezović’s book Balkans in letters: the impressions of an 18th-century Westerner. It is about the book based on epistolary material, created from the pen of an unknown Frenchman who toured the Balkans in the eighteenth century. The book deals with the study of epistolary discourse, which is a current issue of contemporary historical science and other social sciences. The focus is on the importance of letters from a Westerner on the image of the Balkans in the eighteenth century since there are not many sources of similar content.